Hereditary head and neck paraganglioma: from basics to practical consequences. Issue 2 (29th April 2023) - Trache, Mihnea Cristian; Böttcher, Arne; Betz, Christian Stephan
Abstract : Purpose of review: This review summarizes practical recommendations for screening, work-up, and management of hereditary head and neck paragangliomas based on the growing molecular and empirical understanding of this disease. Recent findings: The proportion of hereditary cases among head and neck paragangliomas is significant (∼33 to 50%), and specific genetic alterations may increase the risk of malignancy. Genotyping should be performed for each case, and patients carrying a pathological mutation should be regularly screened for new tumors. Computed tomography (CT), magnetic resonance imaging (MRI), digital subtraction angiography (DSA), and functional positron emission tomography (PET) can provide a reliable preoperative diagnosis in the absence of histology. Comparative data on therapeutic outcome and morbidity now render radiation, stereotactic radiosurgery, and active surveillance preferable over surgery in highly advanced cases of jugulotympanic and vagal paragangliomas, whereas surgery remains the first choice for most carotid body paragangliomas. Summary: Complete paraganglioma removal continues to be the primary therapeutic goal; however, this is sometimes impossible to accomplish with acceptable morbidity. In these cases, therapy selection should focus on preserving cranial nerve function and minimizing both tumor-associated and therapy-associated complications, particularly in genetically predisposed patients. An interdisciplinary approach to the management of hereditary head and neck paragangliomas is strongly recommended.